Jessica Stewart and Megan Pitcavage in volleyball game against MIT - Unknown (Tufts Archival Research Center, 2014)
This date is approximate. 5 x 7 in., photographic print. Back of print reads: "#5 Jessica Stewart; #14 Megan Pitcavage; 10/28 vs MIT; Kate Cohen